Primary bone sarcomas in KSA: A Saudi tumor registry review - Wazzan S. Aljuhani, MD; Abdullah M. Alanazi, MBBS; Mohammad A. Alghafees, MBBS (Journal of Taibah University Medical Sciences, 2021)
الملخص: أهداف البحث: يكشف لنا معدل الانتشار الجغرافي للأورام تأثير البيئة والعرق والمستوى الثقافي على السرطانات. وتهدف هذه الدراسة على سرطان العظام إلى تحديد معدل الحدوث والاختلافات في نمط الورم، وموقع نشأته، ومعدل وفياته باختلاف الجنس، والمناطق، والعمر، والاختلاف في الخصائص بين أنماط الورم. طرق البحث: شملت هذه الدراسة المقارنة الارتجاعية جميع المرضى الذين تم تشخيص إصابتهم بسرطانات عظام أولية بدءا من ١ كانون الثاني/يناير ٢٠١٣ وحتى ٣١ كانون الأول/ديسمبر ٢٠١٧. وتم توليد التكرارات والنسب المئوية حسب المتغيرات الفئوية. تم حساب الوسط الحسابي، والانحراف المعياري للمتغيرات الكمّيّة. وتم حساب معدل الحدوث لكل ورم. النتائج: من بين ٤٥١ مريضا وُجد أن ٢٤٨ مريضا (٥٥٪) يعانون من سرطانات عظمية، وأن ١٦٠ مريضا (٣٥.٥٪) يعانون من سرطان أيوينغ، وأن ٤٣ مريضا (٩.٥٪) يعانون من سرطانات غضروفية. وكان معدل الإصابة هو ١.٥٦ حالة من كل مليون شخص سنويا في السرطانات العظمية، و٠.٩٥ حالة من كل مليون شخص سنويا في سرطان أيوينغ، و٠.٢٧ حالة من كل مليون شخص سنويا في السرطانات الغضروفية. وكان معدل البقيا لمدة ٣ سنوات حوالي ٨٢.٣٪. تم تحديد اختلافات ملحوظة في نمط الورم، وموقع نشأته، ومعدل البقيا لـ٣ سنوات باختلاف العمر والجنس. كما تم أيضا تحديد وجود اختلافات ملحوظة في موقع نشوء الورم، ودرجته، وأساس تشخيصه، وموضعه في أحد الجانبين باختلاف أنماط الأورام. الاستنتاجات: لقد استنتجنا من المنشورات الطبية أن نسب حدوث سرطان العظام الملحوظة كانت أقل بكثير مما تم تحديده عالميا. وإذا فهمنا النمط السلوكي للورم في المنطقة فإننا نستطيع تطوير إستراتيجيات معالجة تعتمد على الخطورة وعلى الاستجابة، وتسمح باتخاذ القرارات بشكل باكر. Abstract: Objectives: The geographical incidence of tumours is usually influenced by the environment, race, and culture. This study aimed to report the incidence and differences in tumour type, site of origin, and mortality across gender, regions, age, and the different characteristics of tumour types. Methods: This retrospective cohort study included all patients diagnosed with primary bone sarcomas from January 1, 2013, to December 31, 2017. Frequencies and percentages were generated for categorical variables. Means and standard deviations were calculated for quantitative variables. A chi-squared test was used to detect differences among categorical variables. Student-t, ANOVA, and Tukey tests were used to detect differences among quantitative variables. Lastly, we calculated the incidence of each tumour type. Results: Of 451 patients, 248 (55%) had osteosarcomas; 160 (35.5%) had Ewing's sarcoma, and 43 (9.5%) had chondrosarcoma. The incidence was 1.56 cases per 1,000,000 per year for osteosarcoma, 0.95 cases per 1,000,000 per year for Ewing's sarcoma, and 0.27 cases per million per year for chondrosarcoma. The three-year survival rate was 82.30%. Significant differences in tumour type, origin site, and three-year survival across age and gender were detected. Similarly, significant differences were also noted in origin site, grade, basis of diagnosis, and lateralisation across tumour types. Conclusions: In our study, the observed bone sarcoma incidence rates were lower than the ones reported worldwide. Understanding the pattern of tumour behaviour in the region will help develop a risk and response-based treatment plan for early decision-making.